2008
DOI: 10.1007/s11627-008-9158-6
|View full text |Cite
|
Sign up to set email alerts
|

Biological characterization of young and aged embryogenic cultures of Pinus pinaster (Ait.)

Abstract: Pinus pinaster (Ait.) somatic embryogenesis (SE) has been developed during the last decade, and its application in tree improvement programs is underway. Nevertheless, a few more or less important problems still exist, which have an impact on the efficiency of specific SE stages. One phenomenon, which had been observed in embryogenic tissue (embryonal mass, EM) initiated from immature seed, has been the loss of the ability to produce mature somatic embryos after the tissue had been cultured for several months.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 41 publications
4
73
1
1
Order By: Relevance
“…In pine species, it is widely accepted that the maturation ability tends to decrease with ECL age. The same observation is true for P. pinaster (Klimaszewska et al 2009). It has been hypothesized that the reduced ability to regenerate from such embryogenic tissues is related to genetic instability.…”
Section: Discussionsupporting
confidence: 69%
“…In pine species, it is widely accepted that the maturation ability tends to decrease with ECL age. The same observation is true for P. pinaster (Klimaszewska et al 2009). It has been hypothesized that the reduced ability to regenerate from such embryogenic tissues is related to genetic instability.…”
Section: Discussionsupporting
confidence: 69%
“…Some examples of mature somatic embryo yield (number) calculated per 1 g of fresh weight: 64 for Abies fraseri (Kim et al 2009), 36 for Abies cephalonica (Krajňáková et al 2009), 187 in Pinus pinaster (Alvarez et al 2013), 321 in Pinus sylvestris (Aronen et al 2009), 269 for Picea glauca (Kong and Yeung 1995), 65 for Picea mariana (Tremblay and Tremblay 1995), 300-960 for hybrid of Larix (Lelu et al 1994). An undesirable phenomenon -loss of ability to produce mature somatic embryos -has been observed in embryogenic tissues of many species (Klimaszewska et al 2009). This phenomenon can be avoid -at least partially -by cryopreservation and subsequent thawing of tissues.…”
Section: Maturation Of Somatic Embryosmentioning
confidence: 99%
“…the cumulative proliferation time from (i) initiation to cryopreservation (4.2 months) and (ii) line regrowth from the cryopreserved stock to the maturation experiment. mDCR modified DCR medium from Gupta and Durzan (1985); mLV modified LV medium from Litvay et al (1985) 2006; Klimaszewska et al 2009;Humánez et al 2012). Biological parameters (dry weight, water content) and biochemical analyses (total protein and carbohydrate contents) showed that cotyledonary se harvested after 10 or 14 weeks did not differ markedly and thus confirmed that harvesting cotyledonary se after 12 weeks is appropriate (Morel et al 2014b).…”
Section: Conversion Of Cotyledonary Somatic Embryo To High-quality Somentioning
confidence: 80%
“…As it is a potent cytokinin with a putative role in ageing and vigour in pine (Valdés et al 2003;Klimaszewska et al 2009), CPPU supplementation during the Fig. 19.2).…”
Section: Initiation From Seed Embryosmentioning
confidence: 99%